Prevention of dipyrone (metamizole) induced inhibition of aspirin antiplatelet effects - Polzin, Amin; Richter, Stefan; Schrör, Karsten; Rassaf, Tienush; Merx, Marc W.; Kelm, Malte; Hohlfeld, Thomas; Zeus, Tobias (Thrombosis and Haemostasis, 2015)
We have recently shown that dipyrone (metamizole), a non-opioid analgesic, can nullify aspirin (acetylsalicylic acid; ASA) antiplatelet effects in patients with coronary artery disease (CAD). In this study, we analysed the aspirin and dipyrone drug-drug interaction in order to identify strategies to prevent the dipyrone induced inhibition of asprin antiplatelet effects. Platelet function was measured by arachidonic acid-induced light-transmission aggregometry, thromboxane (TX) B2–formation by immunoassay. Dipyrone metabolite plasma levels were determined by high-performance-liquid-chromatography (HPLC). In seven healthy individuals, in vitro ASA (30 μM/ 100 μM/ 300 μM/ 1,000 μM) and dipyrone (10 μM) coincubation revealed, that the aspirin and dipyrone interaction can be overcome by increasing doses of aspirin. In 36 aspirin and dipyrone comedicated CAD patients, addition of ASA (30 μM/ 100 μM) in vitro inhibited, but did not completely overcome the dipyrone induced reduction of aspirin antiplatelet effects. Notably, the inhibition of thromboxane formation in aspirin and dipyrone comedicated CAD patients coincided with dipyrone plasma levels. In a cross-over designed study in four healthy individuals, we were able to prove that inhibition of aspirin (100 mg/ day) effects by dipyrone (750 mg/ day) was reversible. Furthermore, aspirin (100 mg/ day) medication prior to dipyrone (750 mg/ day) intake prevented the inhibition of antiplatelet effects by dipyrone in 12 healthy individuals. In conclusion, aspirin medication prior to dipyrone intake preserves antiplatelet effects, circumventing the pharmacodynamic drug-drug interaction at the level of cyclooxygenase-1.Clinical Trial Registration: NCT01402804; http://clinicaltrials.gov/ct2/show/NCT01402804.
Keywords: Aspirin; coronary artery disease; platelets; dipyrone; metamizole